1997
DOI: 10.1023/a:1024983300428
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Distortions in Heavy Gambling

Abstract: A sample of 38 regular and heavy gamblers, recruited through advertisements and not seeking treatment, were asked to describe special strategies, techniques or rituals that they used to increase their chances of winning at gambling in an open-ended interview. The mean South Oaks Gambling Screen Score for the sample was 7.7 with 64% of the sample scoring higher than 4. Their responses reflected multiple means by which the individual believed they were able to control (i.e., active illusory control, passive illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(103 citation statements)
references
References 21 publications
4
95
0
4
Order By: Relevance
“…Gamblers have a tendency to misunderstand their odds of winning (Bandura 1977;Toneatto, Blitz-Miller, Calderwood, Dragonetti, & Tsanos, 1997;Walker 1992;Wohl, Christie, Matheson, & Anisman, 2010). People tend to believe that slot machines randomly select outcomes without replacing them in the full set of outcomes (i.e., with every spin, the odds of winning get better).…”
Section: A Winning Algorithm: Misunderstandings About How Social Casimentioning
confidence: 99%
“…Gamblers have a tendency to misunderstand their odds of winning (Bandura 1977;Toneatto, Blitz-Miller, Calderwood, Dragonetti, & Tsanos, 1997;Walker 1992;Wohl, Christie, Matheson, & Anisman, 2010). People tend to believe that slot machines randomly select outcomes without replacing them in the full set of outcomes (i.e., with every spin, the odds of winning get better).…”
Section: A Winning Algorithm: Misunderstandings About How Social Casimentioning
confidence: 99%
“…Despite erroneous gambling-related cognitions receiving far more attention in recent times, they are rarely investigated with educational populations and as such merit investigation. There are a number of methods available to measure erroneous gambling-related cognitions, such as the "think-aloud" method (Gaboury & Ladouceur, 1989;Griffiths, 1994), interviews (Toneatto, Blitz-Miller, Calderwood, Dragonetti, & Tsanos, 1997), and screens for assessing erroneous cognitions.…”
Section: Introductionmentioning
confidence: 99%
“…Even infrequent gamblers exhibit similar beliefs to disordered gamblers, albeit to a lesser extent [8] [9] [10]. Toneatto, Blitz-Miller, Calderwood, Dragonetti and Tsanos [11] stated that 92% of disordered gamblers held erroneous gambling-related beliefs. The authors found that disordered gamblers often exhibited behavioural patterns reflecting irrational beliefs such as; talking to Electronic Gaming Machines (EGMs), becoming angry when another patron used a favoured machine, hitting EGMs, as well as making statements indicating that the presence of others influenced their "luck" [12].…”
Section: Gambling-related Cognitionsmentioning
confidence: 99%
“…As erroneous beliefs have been shown to play a fundamental role in the devel-opment and maintenance of gambling behaviours, cognitive approaches in the treatment of disordered gambling aim to challenge erroneous beliefs about gambling outcomes [7] [8] [11]. This is achieved through the examination of individually held beliefs, provision of factual information and restructuring of erroneous automatic thoughts [13].…”
Section: Cognitive-behavioural Treatments For Gamblingmentioning
confidence: 99%